Occupational therapy in the analysis and adaptation of workstations for people with disabilities: A case report from the perspective of ergonomics and assistive technology (Research, Society and Development, 2025)
The present work aims to report on the role of the occupational therapist in the analysis and adaptation of workstations for the inclusion of people with disabilities, focusing on Ergonomics and Assistive Technology. This is a case study article conducted at a public educational institution located in the city of Recife-PE, involving a public servant (architect) with a physical disability. The actions were developed through an extension project linked to a laboratory in the Department of Occupational Therapy at the University. During the evaluation phase, the characterization of the disability, the environment, and the workstation was carried out, along with the application of standardized tests and instruments aimed at assessing impairments in bodily functions and the impacts on daily activities. In the intervention process, visits to the workstation were made, adaptations and adjustments were implemented for furniture and tools, as well as the prescription and fabrication of orthoses for the upper limbs. It is concluded that the occupational therapist, in the work context, with the support of Ergonomics, can significantly contribute to the inclusion of people with disabilities. Therefore, the use of assistive technology devices emerges as an alternative to promote improvements in functional status. Finally, the need for studies that evaluate and monitor the impact of Occupational Therapy interventions is emphasized, with a view to disseminating scientific knowledge in this area and providing solutions to the target audience.